2016
DOI: 10.1016/j.ejor.2015.10.035
|View full text |Cite
|
Sign up to set email alerts
|

CEO compensation and bank efficiency: An application of conditional nonparametric frontiers

Abstract: The paper, by incorporating the latest developments on the probabilistic approach of efficiency measurement, (Bădin et al., 2012) investigates in a dynamic context the effect of Chief Executive Officer (CEO) bonus and salary payments on banks' technical efficiency levels. We apply time-dependent conditional efficiency estimates to analyze a sample of 37 US banks for the period from 2003 to 2012. The empirical evidence reveals a non-linear relationship between CEO bonus and salary payments and banks' efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 69 publications
1
21
0
1
Order By: Relevance
“…Another natural path toward further improvement would be to employ the recently developed theory and testing procedures from Kneip et al (2015;. The third natural direction of future research would be to employ alternative methods of estimating efficiency, such as ‗Imprecise DEA', ‗Context-Dependent Assurance Region DEA', or DEA with non-homogeneous firms (see Zhu, 2004;Cook et al, 2006;Cook and Zhu, 2008), Stochastic DEA (Simar and Zelenyuk, 2011) as well as alternative methods to analyse the influence of factors on efficiency, as based on recent work by Bădin et al (2010), Bădin et al (2012), Daraio and Simar (2014), Mastromarco and Simar (2015), Tzeremes (2015) and Matousek and Tzeremes (2016), Park et al (2015), Simar et al (2017) among others. Finally, application of all these methods to larger or different data sets would also be interesting.…”
Section: Discussionmentioning
confidence: 99%
“…Another natural path toward further improvement would be to employ the recently developed theory and testing procedures from Kneip et al (2015;. The third natural direction of future research would be to employ alternative methods of estimating efficiency, such as ‗Imprecise DEA', ‗Context-Dependent Assurance Region DEA', or DEA with non-homogeneous firms (see Zhu, 2004;Cook et al, 2006;Cook and Zhu, 2008), Stochastic DEA (Simar and Zelenyuk, 2011) as well as alternative methods to analyse the influence of factors on efficiency, as based on recent work by Bădin et al (2010), Bădin et al (2012), Daraio and Simar (2014), Mastromarco and Simar (2015), Tzeremes (2015) and Matousek and Tzeremes (2016), Park et al (2015), Simar et al (2017) among others. Finally, application of all these methods to larger or different data sets would also be interesting.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, by conditioning on time, we will be able to analyze the efficiency behavior of our sample of European banks, allowing us to account for the dependence of the data‐generating process (DGP) on time effects across the period of the financial crisis (Tzeremes, 2015). This framework is becoming increasingly popular in the literature on conditional efficiency due to its ability to take into account the time‐dependent nature of a DGP (see, for example, Tzeremes, 2015; Matousek and Tzeremes, 2016; Cordero et al., 2017; Halkos and Managi, 2017; Broadstock et al., 2019; Halkos and Bampatsou, 2019; Polemis and Tzeremes, 2019; Pedraja et al., 2020; Polemis et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of previous studies applies multiple regression analysis (MRA) in order to examine firm performance and its determinants, therefore assuming a linear relationship (Sun et al, 2013;Sheikh et al, 2018). Another strand in the literature argues that this relationship is non-linear and found various types of asymmetries (Fong et al, 2015;Matousek and Tzeremes, 2016). This study uses the complexity theory tenets in order to examine possible asymmetrical relationships between antecedents (CEO's compensation and age among others) and the outcome condition ( firm's performance).…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that cash bonus and firm performance were positively related, while equity-based compensation was negatively related with firm performance. Matousek and Tzeremes (2016) examined the effect of CEO compensation on the bank efficiency levels and found a significant non-linear relationship among them. Furthermore, the results indicated than CEO salary and bonus affected differently the level of the efficiency.…”
mentioning
confidence: 99%